Linking microbial C:N:P stoichiometry to microbial community and abiotic factors along a 3500‐km grassland transect on the Tibetan Plateau. Issue 12 (24th August 2016) - Chen, Yong‐Liang; Chen, Lei‐Yi; Peng, Yun‐Feng; Ding, Jin‐Zhi; Li, Fei; Yang, Gui‐Biao; Kou, Dan; Liu, Li; Fang, Kai; Zhang, Bei‐Bei; Wang, Jun; Yang, Yuan‐He
Abstract: Aim: To explore large‐scale patterns and the drivers of carbon:nitrogen:phosphorus (C:N:P) stoichiometry in heterotrophic microbes. Location: A 3500‐km grassland transect on the Tibetan Plateau. Methods: We investigated large‐scale C:N:P stoichiometry patterns in the soil microbial biomass and their relationships with abiotic factors and soil microbial community structures by obtaining soil samples from 173 sites across the Tibetan alpine grasslands. Results: C:N:P ratios in the soil microbial biomass varied widely among grassland types, with higher microbial C:N, C:P and N:P ratios in the alpine steppe than the alpine meadow. The soil microbial C:N:P ratio (81:6:1) in the alpine steppe was significantly wider than the global average (42:6:1). Combined stepwise regression and generalized additive models revealed that variations in the microbial C:N ratio were primarily related to abiotic variables, with the microbial C:N ratio exhibiting a decreasing trend along the precipitation gradient. In contrast, variations in microbial C:P and N:P ratios were primarily associated with shifts in the community structure of soil microbes. The microbial C:P and N:P ratios were both negatively associated with all components of the soil microbial communities. However, the fungi to bacteria ratio only regulated the microbial C:P ratio. Main conclusions: These results demonstrate that microbial C:N:P stoichiometry exhibits significant flexibility across various ecosystem types. This flexibility is partly induced by shifts in microbial community structure and variations in environmental conditions.